2005
DOI: 10.1261/rna.2250405
|View full text |Cite
|
Sign up to set email alerts
|

Exon repression by polypyrimidine tract binding protein

Abstract: Polypyrimidine tract binding protein (PTB) is known to silence the splicing of many alternative exons. However, exons repressed by PTB are affected by other RNA regulatory elements and proteins. This makes it difficult to dissect the structure of the pre-mRNP complexes that silence splicing, and to understand the role of PTB in this process. We determined the minimal requirements for PTB-mediated splicing repression. We find that the minimal sequence for high affinity binding by PTB is relatively large, contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
177
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(192 citation statements)
references
References 53 publications
(96 reference statements)
13
177
2
Order By: Relevance
“…In agreement with previous work, PTB-repressed exons were associated with PTB binding upstream of or within the regulated exon. However, in contrast to some well-studied PTB-repressed exons, including -tropomyosin (Tpm1) exon 3 [14,15] and SRC N1 exon [16], we found no general tendency for PTB binding downstream of repressed exons. In contrast, the newly characterized PTB-activated exons were clearly associated with PTB binding on the downstream side of the exon [12].…”
Section: Ptb Splicing Mapscontrasting
confidence: 99%
See 1 more Smart Citation
“…In agreement with previous work, PTB-repressed exons were associated with PTB binding upstream of or within the regulated exon. However, in contrast to some well-studied PTB-repressed exons, including -tropomyosin (Tpm1) exon 3 [14,15] and SRC N1 exon [16], we found no general tendency for PTB binding downstream of repressed exons. In contrast, the newly characterized PTB-activated exons were clearly associated with PTB binding on the downstream side of the exon [12].…”
Section: Ptb Splicing Mapscontrasting
confidence: 99%
“…To fully understand how PTB functions, it is important to know how many PTB molecules bind to target RNAs. Conventional biochemical assays, such as electrophoretic mobility shift or filter-binding, have shown that splicing substrates typically bind more than one PTB molecule [14][15][16]32]. However, these analyses have used pure recombinant PTB, which could easily lead to overestimates of the true number of molecules bound in vivo, where non-specific binding will be suppressed by the numerous other proteins that coat the RNA.…”
Section: Counting Proteins In Complexesmentioning
confidence: 99%
“…DNA Constructs. PTB1, nPTB, and reporter plasmid DS9-175 were prepared as described (26). The three mutations in PTB1 (PTB 3Mut) were made with two consecutive PCR reactions using the primers 2Mut-F, 2Mut-R, 1Mut-F, and 1Mut-R (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…To test how functionally important is the interface between RRM3 and RRM4, we used a splicing reporter assay (25) in HeLa cells with a reporter gene containing two separate PPTs separated by a long linker (DS9-175) (26). In a control experiment without protein over expression, the alternative exon is 80% included, whereas only 34% is included when PTB is transfected and overexpressed.…”
Section: Rna Looping By Ptb34 Is Essential For Efficient Splicing Regmentioning
confidence: 99%
“…PTB is one of the most frequently encountered ITAFs and was found to be implicated in IRES-mediated translation of several Figure 1. Polypyrimidine tract binding protein (PTB) is a ubiquitous regulator of alternative splicing that influences different types of alternative-splicing events (a) PTB represses the N1 "cassette-exon" in the c-src pre-mRNA [7,9,10,103]. (b) PTB represses the "mutually exclusive" SM exon of the a-actinin mRNA [12,13].…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%